Fabrication, Optimization, and Pharmacological Assessment of Apigenin-Loaded Nanoemulsion Gels: A Novel Topical Approach for the Treatment Urinary Tract Infections - Kapil Mahajan, Renuka; Chandra Biswas, Palash; Pawar, Neelam; Rathaur, Himanshi; Kaur Walia, Manpreet; Rahamanulla, Abdul; Sharma, Prashant; Nirmala, R. (Journal of Neonatal Surgery, 2025)
The present study focused on the formulation, characterization, and evaluation of a nanoemulsion-based gel incorporating apigenin, chitosan, and eucalyptus oil for enhanced drug delivery and antibacterial activity. Three formulations—blank nanoemulsion, chitosan-based nanoemulsion gel, and eucalyptus oil nanoemulsion—were developed and subjected to physicochemical characterization and thermodynamic stability testing. The formulations exhibited optimal droplet size (59.54–87.48 nm), zeta potential (-22.4 to +27.2 mV), and polydispersity index (0.119–0.338), ensuring colloidal stability. FTIR analysis confirmed successful drug incorporation without significant chemical interactions. The drug content was 95.80 ± 1.26% for the nanoemulsion and 93.75 ± 1.30% for the nanoemulsion gel, indicating efficient entrapment. The in vitro drug release study demonstrated a sustained release profile, with NEMULF2 (nanoemulsion) releasing 81.56% and NEMULGF3 (nanoemulsion gel) releasing 71.87% over 12 hours, confirming the gel’s controlled-release properties. The antibacterial study revealed a concentration-dependent inhibition against Pseudomonas aeruginosa (24.86 mm at 500 µg/mL) and Escherichia coli (26.65 mm at 500 µg/mL), significantly surpassing the pure drug's efficacy. The findings suggest that nanoemulsion-based gels enhance drug stability, bioavailability, and antimicrobial efficacy, making them promising candidates for topical therapeutic applications.